PEDOMAN INTERPRETASI RADIOGRAF LESI-LESI DI RONGGA MULUT - Supriyadi Supriyadi (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
The interpretation of dental radiograph was be important to support of diagnose a specially was diagnose of oral lessions. The purpose of this paper was to give of dental radiograph interpretation guidens so can to improve the accuracy of diagnose. The guidens of dental radiograph was to enclosed: 1) the meaning and objective of of dental radiograph interpretation,2) the commonly principle of dental radiograph interpretation, 3) the systematic procedure of dental radiograph interpretation, and 4) the differential diagnose steps of oral lessions